2013
DOI: 10.1371/journal.pbio.1001562
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Homologue of the Amyloid Precursor Protein Is a Conserved Modulator of Wnt PCP Signaling

Abstract: The Drosophila homolog of the Alzheimer's disease protein APP, known as APPL, regulates axon growth during brain development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(115 citation statements)
references
References 41 publications
9
104
0
Order By: Relevance
“…APPL knockout Drosophila are viable but have subtle behavioral defects (including conditional learning defects) (Luo et al, 1992) and defects in maintenance of synaptic boutons at the neuromuscular junction (NMJ) (Torroja et al, 1999b) and are more vulnerable to brain injury (Leyssen et al, 2005). APPL also modulates the Wnt-planar cell polarity (PCP) pathway required for axonal outgrowth during neuronal development (Soldano et al, 2013). Finally, deletion mutations of the Drosophila APPL gene, or animals overexpressing either APPL, human APP, or the C terminus of human APLP2 exhibit Ab-independent defects in axonal transport mediated by the conserved cytoplasmic C terminus (Goldstein, 2012;Gunawardena and Goldstein, 2001;Rusu et al, 2007;Torroja et al, 1999a).…”
Section: Possible Functions Of App Family Members In Brain Developmenmentioning
confidence: 99%
See 2 more Smart Citations
“…APPL knockout Drosophila are viable but have subtle behavioral defects (including conditional learning defects) (Luo et al, 1992) and defects in maintenance of synaptic boutons at the neuromuscular junction (NMJ) (Torroja et al, 1999b) and are more vulnerable to brain injury (Leyssen et al, 2005). APPL also modulates the Wnt-planar cell polarity (PCP) pathway required for axonal outgrowth during neuronal development (Soldano et al, 2013). Finally, deletion mutations of the Drosophila APPL gene, or animals overexpressing either APPL, human APP, or the C terminus of human APLP2 exhibit Ab-independent defects in axonal transport mediated by the conserved cytoplasmic C terminus (Goldstein, 2012;Gunawardena and Goldstein, 2001;Rusu et al, 2007;Torroja et al, 1999a).…”
Section: Possible Functions Of App Family Members In Brain Developmenmentioning
confidence: 99%
“…APP C99, but not C83, is preferentially phosphorylated on Thr743 (Lee et al, 2003), and Pin1 binds C99 but not full-length APP nor C83, indicating that differential APP cleavage controls specific downstream events (Akiyama et al, 2005). One such event might be signaling through the Wnt-PNP receptor complex (Soldano et al, 2013). C99 interacts with multiple proteins of this complex (Vangl2, Frizzeld, and Frizzeld5) that regulate cellular polarity and axonal outgrowth, but whether this is phospho dependent has not been tested (Soldano et al, 2013).…”
Section: App Proteolytic Products: Unique Proteins With Specialized Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Like APP, APPL is subject to proteolytic processing by α, β, and γ-secretases that generate an analogous spectrum of cleavage fragments, including sAPPs, CTFs, AICDs, and an Aβ-like peptide (Luo et al, 1995; Greeve et al, 2004; Carmine-Simmen et al, 2009; Poeck et al, 2012). Also like mammalian APP, APPL plays important roles in the developing nervous system, participating in the control of neuronal migration and synaptic plasticity (Torroja et al, 1999; Ashley et al, 2005; Ramaker et al, 2013; Soldano et al, 2013; Bourdet et al, 2015). Notably, studies in Drosophila have shown that defects caused by the loss of APPL can be rescued by the expression of human APP 695 (Luo et al, 1992; Wentzell et al, 2012), indicating that these proteins are both structurally and functionally homologous.…”
Section: Introductionmentioning
confidence: 99%
“…melanogaster has been used extensively to study the role of the APP homolog APPL in the context of axonal growth. Recently, it has been shown that Appl null flies (Appl d ) display developmental axonal growth defects in mushroom bodies, which house a neuronal population that is important for learning and memory (Soldano et al, 2013), as well as in retinal axons (Mora et al, 2013). The expression of full-length APPL, but not sAPPL nor a membranetethered form lacking the conserved C-terminus, rescued this phenotype, suggesting that the APPL C-terminus is crucial for its function.…”
Section: The Role Of App In Neurite Outgrowth and Guidancementioning
confidence: 99%